The Intervention Programs To Reduce Stigma And Discrimination In People Living With HIV/ AIDS (PLWHA) - Wahyu Wirawan Triyono; Fitra Arsy Nur Cory'ah (poltekkes kemenkes mataram, 2020)
The case of HIV / AIDS is still a global problem and a serious concern from all parties, especially in Central Lombok. HIV/AIDS-related stigma and discriminatory attitudes deter the effectiveness of HIV/AIDS prevention and care programs. The Intervention efforts that have been by Central Lombok for the mobile VCT program through Communication, Information and Education on PLWHA (People Living with HIV/AIDS), Static VCT Programs and Internal In House Training Programs in Praya Hospital and others.This research examines the stigma and discrimination associated with interventions made by the Central Lombok. This type of research is qualitative with a phenomenological approach design, data collection through in-depth interviews and document search. Data analysis with data reduction, data presentation, conclusion drawing and verification. The results revealed that their PLWHA had experienced stigma and discrimination, health workers and the general public had positive and negative views related to still, they discriminated who were in the community. The conclusion in this research is that stigma and discrimination against PLWHA are still prevalent in the community and intervention efforts made in providing advocacy to health workers, the general public has been endeavored to reduce these problems.